Counseling students’ experiences in an Islamic-based counseling course - Sumari, M. (2015)
The purpose of this study was to describe the experiences of learning and consequent development of twelve students enrolled in a four-year undergraduate counseling program at a higher institution of learning in Malaysia. The students' ages ranged from 20 to 24 years. Participants described their learning experiences after taking a three-credit semester-long course on Islamic-based counseling, which was an attempt in integrating religion and spirituality into counselor training. An experiential learning theory served as the framework of reference, and a qualitative research design was adopted. Results revealed four major themes: (1) increased understanding about Islamic-based counseling, (2) gaining better self-understanding, (3) applicability to daily practice, and (4) enhancing professional competence as a counselor. Finally, implications for research, counselor education and training, and clinical practice were discussed.